PENGARUH STIMULASI KUTANEUS SLOW STROKE BACK MASSAGE TERHADAP INTENSITAS NYERI OSTEOARTRITIS PADA LANSIA - Anita Gandaria Purba; Kuat Sitepu; Kardina Hayati; Arfah May Syara; Reni Aprinawaty Sirait; Nurhamidah Pohan (JURNAL PENGMAS KESTRA (JPK), 2021)
Osteoarthritis (OA) also known as degenerative joint disease is the most common in all forms of arthritis and causes pain and disability in the elderly. This disease is characterized by progressive loss of joint cartilage, synovitis (inflammation of the synovium that lines the joints), joint pain, stiffness, and loss of joint movement (Lemone, 2018:1679). Cutaneous stimulation that can be done is Slow-Stroke Back Massage. The correct use of cutaneous stimuli: slow-stroke back massage can reduce pain perception and help reduce muscle tension which can reduce pain intensity, besides that it can also cause dilation of blood vessels and improve blood circulation in the tissue. The purpose of this study was to determine the Effect of Cutaneous Stimulation of Slow Stroke Back Massage on Osteoarthritis Pain Intensity in the Elderly at Susoh Health Center, in 2021. This type of research is experimental. Data were analyzed for bivariate calculations in this study using Pair Samples t-test with the provisions of 0.05. Based on the results of statistical tests using the paired sample t-test, the p value (= 0.000) < (= 0.05) can be concluded that the hypothesis in the study is accepted, meaning that there is a difference in the mean pain intensity before and after cutaneous slow stroke stimulation.